Fractional Counting Understanding of Students in Jagoan Muhammadiyah Islamic Elementary School (MI Muhammadiyah Jagoan), Boyolali - Prabowo, Wisnu Aji (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Counting skill is a basic ability that must be possessed by students as a provision in everyday life. Fractions understanding is not only a number calculation but also a problem-solving process. Therefore, students must be able to understand fractional calculations before understanding the next material. This research was a qualitative descriptive study with a sample of 20 4th-grade students in Jagoan Muhammadiyah Islamic Elementary School (MI Muhammadiyah Jagoan), Sambi, Boyolali. Data collection techniques were interviews, observation, and study documents. The triangulation technique was employed to achieve data validity. Data analysis used interactive techniques with stages of data collection, data reduction, data presentation, and drawing conclusions. The purpose of this research was to observe the students' understanding of counting fractions. The results revealed that most students were still deficient in understanding fractions. It could be seen from the classical average of students that the score was only 16, which was still far below the Minimum Completeness Criteria (KKM) of 65. Of the 20 students, none of them achieved a score above the KKM.